HOW TO DEVELOP AN E-LKPD WITH A SCIENTIFIC APPROACH TO ACHIEVING STUDENTS' MATHEMATICAL COMMUNICATION ABILITIES? - Wahyu Hidayat; Usman Aripin (IKIP Siliwangi and I-MES, 2023)
This research aims to look into the growth and effectiveness of E-LKPD on the mathematical communication skills of seventh-grade junior high school students. The design research development study was used. This study is divided into two parts: preliminary (preliminary study and design of E-LKPD) and formative evaluation (evaluation and revision). The research subjects included 49 SMP Negeri 3 Ngamprah's class VIII students. The research instrument had interview sheets, expert validation sheets, observation sheets, student response questionnaires, and five questions about mathematical communication skills. Lines and angles were used in this study as the material. Data processing techniques in the development process use the Likert Scale type of measurement scale to calculate the percentage of each indicator with the help of Canva and test the effectiveness of the E-LKPD using Inferential Statistics with the Wilcoxon test with the help of SPSS. According to the study's findings, the feasibility of LKPD is Eligible. The study's results also show that an E-LKPD influences students' mathematical communication abilities, indicating that the developed E-LKPD has effectiveness.